Measuring the multidimensional reputation of a medicines regulatory agency: development and validation of a public-oriented scale - Son, Kyung-Bok (Frontiers in Medicine, 2025)
ObjectiveThe reputation of public agencies, encompassing the dimensions of performance, morality, procedure, and technical competence, is fundamental to understanding their behavior. However, standardized, individual-level measures of reputation suitable for surveys targeting the general public are lacking. This study aims to develop and validate a survey instrument for the general public to measure the multi-dimensional reputation of public agencies, with a focus on South Korea’s medicines regulatory agency.MethodsSurvey items were developed based on previous literature, refined through expert consultation, and validated through a population survey. The validation study involved 1,000 participants from the public, selected using a quota sampling method stratified by age, sex, and region, according to the South Korean census. Validity was assessed through exploratory factor analysis and hypothesis testing, while reliability was evaluated using internal consistency.ResultsExploratory factor analysis identified a three-dimensional structure of reputation, encompassing performance, procedure, and technical competence, while morality was not distinctly identified as a separate dimension. Construct validity, including convergent and discriminant validity, was confirmed. The internal consistency of the three dimensions was acceptable, with Cronbach’s alpha coefficients ranging from 0.87 to 0.91. The overall reputation of the medicines regulatory agency was measured at 72 out of 100. The specific dimension scores were as follows: 74 for technical competence, 71 for performance, and 70 for procedure.ConclusionThe agency should recognize the multidimensional nature of reputation and foster an environment that enables the public to observe and evaluate these dimensions. Reputation management strategies should emphasize not only technical expertise but also performance and procedural aspects to ensure a well-rounded reputation.